EVALUASI MODEL KIRKPATRICK PADA PROGRAM PELATIHAN PENDIDIK DAN TENAGA KEPENDIDIKAN DI SMPIT BAHRUL ULUM SUBANG - Didin; Jahani (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
This study aims to evaluate the effectiveness of the training program for educators and educational staff at SMPIT Bahrul Ulum Subang using the Kirkpatrick Model, which consists of four levels of evaluation: reaction, learning, behavior, and results. A qualitative approach was employed through in-depth interviews, observations, and document analysis involving training participants and the school environment. The findings indicate that participants showed positive reactions to the training materials, instructional methods, and facilitators. In terms of learning outcomes, there was a significant improvement in participants’ knowledge and skills after attending the training. Behavioral changes were also evident through the application of acquired competencies in daily work activities. At the results level, the training contributed to improved student academic performance and enhanced school operational efficiency. The study concludes that the training program was effective in strengthening the professional competencies of educators and educational staff. Despite limitations related to context and resources, the findings are expected to serve as a reference for the development of more sustainable educational training programs